PELAKSANAAN OTONOMI DESA DI BIDANG KEUANGAN (STUDI OPTIMALISASI PADES DI DESA HANGTUAH KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR TAHUN 2012-2014) - Rudi Setiyawan; Auradian Marta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Implementation of Rural Village Government in the District HangtuahPerhentian Raja has not been established to the maximum, this is because thevillage government authority to regulate duty personnel structure and budgetfunctions required to move the organization and the ability to serve thecommunity of the village have not been up anyway.This research was conducted in the Hangtuah village of Perhentian RajaDistrict of Kampar. The data used in this study is Primary data and secondarydata. Data collection through in-depth interviews and documentation. This studyuses qualitative descriptive method because the retrieval of data from informantsdepth interviews of informants related. So that the problem in this case is How theVillage Government efforts in improving the District Revenue Hangtuah VillagePerhentian Raja Kampar years 2012-2014 and What are the factors that affect thegovernment's efforts in exploring the potential of rural village In the village ofPerhentian Raja Hangtuah District of Kampar Regency in 2012 -2014.From the results of this study are described that attempt VillageGovernment in Increasing Revenue Village Hangtuah District of Perhentian RajaKampar is to further strengthen the implementation of Village Autonomy inparticular in the implementation of development it is necessary to increase againTraffic village officials in management, education, whether it is training for cadresvillage so untapped potential can be utilized for the sake of the welfare of thevillage. Factors Inhibiting Autonomy Village in the Village Hangtuah is a factorInfrastructures, at least revenue-generating asset village Village, Low salaries /honorarium villageKeywords: Implementation, Village Autonomy, Finance